Changes within the P681 residue of spike dictate cell fusion and syncytia formation of Delta and Omicron variants of SARS-CoV-2 with no effects on neutralization or infectivity - Alona Kuzmina; Dina Korovin; Ido Cohen lass; Nofar Atari; Aner Ottolenghi; Pan Hu; Michal Mandelboim; Benyamin Rosental; Elli Rosenberg; Felipe Diaz-Griffero; Ran Taube (Heliyon, 2023)
The rapid spread and dominance of the Omicron SARS-CoV-2 lineages have posed severe health challenges worldwide. While extensive research on the role of the Receptor Binding Domain (RBD) in promoting viral infectivity and vaccine sensitivity has been well documented, the functional significance of the 681PRRAR/SV687 polybasic motif of the viral spike is less clear. In this work, we monitored the infectivity levels and neutralization potential of the wild-type human coronavirus 2019 (hCoV-19), Delta, and Omicron SARS-CoV-2 pseudoviruses against sera samples drawn four months post administration of a third dose of the BNT162b2 mRNA vaccine. Our findings show that in comparison to hCoV-19 and Delta SARS-CoV-2, Omicron lineages BA.1 and BA.2 exhibit enhanced infectivity and a sharp decline in their sensitivity to vaccine-induced neutralizing antibodies. Interestingly, P681 mutations within the viral spike do not play a role in the neutralization potential or infectivity of SARS Cov-2 pseudoviruses carrying mutations in this position. The P681 residue however, dictates the ability of the spike protein to promote fusion and syncytia formation between infected cells. While spike from hCoV-19 (P681) and Omicron (H681) promote only modest cell fusion and formation of syncytia between cells that express the spike-protein, Delta spike (R681) displays enhanced fusogenic activity and promotes syncytia formation. Additional analysis shows that a single P681R mutation within the hCoV-19 spike, or H681R within the Omicron spike, restores fusion potential to similar levels observed for the Delta R681 spike. Conversely, R681P point mutation within the spike of Delta pseudovirus abolishes efficient fusion and syncytia formation. Our investigation also demonstrates that spike proteins from hCoV-19 and Delta SARS-CoV-2 are efficiently incorporated into viral particles relative to the spike of Omicron lineages. We conclude that the third dose of the Pfizer-BNT162b2 provides appreciable protection against the newly emerged Omicron sub-lineages. However, the neutralization sensitivity of these new variants is diminished relative to that of the hCoV-19 or Delta SARS-CoV-2. We further show that the P681 residue within spike dictates cell fusion and syncytia formation with no effects on the infectivity of the specific viral variant and on its sensitivity to vaccine-mediated neutralization.